Pengaruh Brand Image Terhadap Keputusan Pembelian Produk Rabbani Pada Toko Salamah - Bayu Arnanda; Uswah Hasanah (CERED Indonesia Institute, 2023)
The purpose of this study was to examine the effect of brand image on purchasing decisions for rabbani products at salamah stores. The method used is a quantitative method using a sample of 30 and data collection techniques in this study using literature studies and questionnaires. Data analysis techniques used validity test, simple linear regression test, and hypothesis. The prerequisite test in this study uses the classical assumption test. The results of the study prove that the tcount value is 2.961> ttable 1.697 with a significance level of 0.006, which means that the hypothesis in this study accepts Ha and rejects H0. The conclusion of this study is that brand image has a significant positive effect on purchasing decisions for rabbani products at salamah stores by 23.8%..